Factors Related to Exclusive Breastfeeding During The COVID-19 Pandemic: Literature Review - Kartika, Maudy (Rajaki of Tulip Medika Publisher, 2023)
Background: The COVID-19 pandemic has created several challenges in exclusive breastfeeding, even though WHO has provided recommendations to continue exclusive breastfeeding during the COVID-19 pandemic. Purpose: This study aims to summarize the factors that can affect breastfeeding mothers during the COVID-19 pandemic. Methods: This research is a literature review. Thematic articles were selected from 2020-2023 from the electronic databases Science Direct, PubMed, and Google Scholar. Researchers used the PRISMA method. Result: From 170 articles, 15 studies were reviewed, and finally, only 10 were analyzed. From the articles analyzed, various supports from husbands, families, and health workers, information support, motivation, beliefs, self-efficacy, delivery settings, age, education level, and work situations influence exclusive breastfeeding. Conclusion: The factors that most influence the practice of exclusive breastfeeding are support from husbands, and family, support from health workers, and information support. It is hoped that policymakers and health workers will be more active in making socialization programs about the importance of providing exclusive breastfeeding during the COVID-19 pandemic.